Combinatorial Inhibition of Cell Surface Receptors Using Dual Aptamer-Functionalized Nanoconstructs for Cancer Treatment - Hyojin Lee; Tae Hee Kim; Daechan Park; Mihue Jang; Justin J. Chung; Soo Hyun Kim; Sang-Heon Kim; Kwan Hyi Lee; Youngmee Jung; Seung Ja Oh (MDPI AG, 2020)
Membrane receptors overexpressed in diseased states are considered novel therapeutic targets. However, the single targeting approach faces several fundamental issues, such as poor efficacy, resistance, and toxicity. Here, we report a dual-targeting strategy to enhance anti-cancer efficacy via synergistic proximity interactions between therapeutics and two receptor proteins. Importantly, we report the first finding of an interaction between c-Met and nucleolin and demonstrate the therapeutic value of targeting the interaction between them. Bispecific nanocarriers densely grafted with anti-c-Met and -nucleolin aptamer increased the local concentration of aptamers at the target sites, in addition to inducing target receptor clustering. It was also demonstrated that the simultaneous targeting of c-Met and nucleolin inhibited the cellular functions of the receptors and increased anti-cancer efficacy by altering the cell cycle. Our findings pave the way for the development of an effective combinatorial treatment based on nanoconstruct-mediated interaction between receptors.